Criticism of Mixed Marriage and Child Citizenship Rights: Family Law Reform in Indonesia - Abdul Aziz; Ali Mutakin (SHAHIH: Journal of Islamicate Multidisciplinary, 2024)
Mixed marriage and children's citizenship rights in Indonesia are increasingly becoming relevant topics in the midst of globalization and high social mobility. This study aims to analyze criticism of existing regulations and explore the need for more inclusive and responsive family law reform. The methodology used in this study includes a qualitative analysis of laws and regulations. The data collection techniques applied include a thorough literature study of various sources, including books, journal articles, and relevant legal documents. The results of the study show that the current laws, especially Law No. 1 of 1974 on Marriage and Law No. 12 of 2006 on Citizenship, are still inadequate in accommodating the rights of children from mixed marriages. Legal uncertainties regarding child citizenship as well as complex registration procedures lead to discrimination and hinder children's access to basic services. Therefore, comprehensive reforms are needed to ensure the protection of the rights of children and women, as well as to harmonize national laws with international standards. This research contributes to a broader discussion on the importance of family law reform to realize justice and welfare for all family members in Indonesia.